Conocemos nuestros gustos y preferencias - Esquivel Rodríguez, Yris Kalleti (2019)
This demonstrative learning session “we know our gusts and preferences” for children aged 03 at the initial education level of regular basic education aims to learn the development of the competition “build your needs, sensations, interests and preferences; differences from those of others through words, actions, gestures or movements._x000D_ The class is endorsed in socio – constructivist theories within the framework of the competency curriculum, considering pedagogical processes in the area of social staff and with an emphasis on formative evaluation